2018
DOI: 10.1111/ppl.12839
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate affects transcriptional regulation of UPBEAT1 and ROS localisation in roots of Zea mays L.

Abstract: Nitrogen (N) is an indispensable nutrient for crops but its availability in agricultural soils is subject to considerable fluctuation. Plants have developed plastic responses to external N fluctuations in order to optimise their development. The coordinated action of nitric oxide and auxin seems to allow the cells of the root apex transition zone (TZ) of N‐deprived maize to rapidly sense nitrate (NO3−). Preliminary results support the hypothesis that reactive oxygen species (ROS) signalling might also have a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 66 publications
2
23
1
Order By: Relevance
“…However, the genes specifically expressed in root hair cells, such as ROBHC/RHD2 and RHD6, which may be induced by nutrients, seem to validate this relationship ( Table 1). A recent study further confirmed that nitrite could affect the expression of UPBEAT1 and localization of ROS in Zea mays L. roots (Trevisan et al, 2019).…”
Section: Nutrient Stress Regulates Root Hair Developmentmentioning
confidence: 74%
See 1 more Smart Citation
“…However, the genes specifically expressed in root hair cells, such as ROBHC/RHD2 and RHD6, which may be induced by nutrients, seem to validate this relationship ( Table 1). A recent study further confirmed that nitrite could affect the expression of UPBEAT1 and localization of ROS in Zea mays L. roots (Trevisan et al, 2019).…”
Section: Nutrient Stress Regulates Root Hair Developmentmentioning
confidence: 74%
“…•− ) gradient distribution in the root meristem (Tsukagoshi et al, 2010;Perilli et al, 2012;Del Pozo, 2016). This distribution is affected by the nitrate nutrient (Trevisan et al, 2019).…”
Section: Gradient Distribution Of Ros Regulates Root Stem Cell Differmentioning
confidence: 99%
“…A number of genes belonging to the group of nitrate transporters and of ROS metabolism were selected basing both on previous results (Trevisan et al 2017 [20]) and on their putative physiological role (Table 1). Table 1.…”
Section: Biostimulant Regulation Of Gene Expressionmentioning
confidence: 99%
“…However, no results on its effects in abiotic stress conditions were gained until now. Our various results with this species indicate that maize is able to sense and rapidly respond to nutritional fluctuations already after hours or minutes of treatment [17][18][19][20]. Therefore in the present work, we tried to deepen the effects of APR®, supplied in in hydroponic, in affecting the early response of maize seedlings to abiotic stresses.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the presence of either nitrate or ammonium clearly affect the content of various metabolites and the activity of many enzymes [16][17][18][19][20][21]. Actually, metabolic and signaling responses to N provision also include redox homeostasis adjustments, which in turn may influence the global response to abiotic stress [22][23][24][25]. Over the past few decades, besides improving crop productivity [26], the intensification of the application of N fertilizers also triggered adverse and sometimes conflicting effects on plant-pathogen interactions [27] and plant disease development [28].…”
Section: Introductionmentioning
confidence: 99%